From Analysis to Classification: Automation of Residential Building Classification Using GIS Tools - Vogrinec, Mara; Koblar, Simon; Fikfak, Alenka; Grom, Janez P. (Igra ustvarjalnosti, 2024)
The research focuses on the development of a GIS analytical tool for the classification of residential buildings, designed to support spatial planning and urban analysis in Slovenia. Traditional spatial data analysis methods are time-consuming and often rely on manual procedures, limiting their efficiency and applicability for large-scale projects. Developed tool integrates morphological analysis within a GIS environment to enable the automated classification of buildings based on various typologies and patterns, representing a significant advancement in the automation and standardization of spatial data analysis. The tool integrates data from the real estate cadastre with established rules from literature, allowing for consistent classification of buildings into detached and connected types, with further classification by typology and building pattern. The development process utilized PostgreSQL with the PostGIS extension for data processing and QGIS for visualization, ensuring accessibility through open-source software. The tool was tested in three Slovenian cities - Maribor, Velenje, and Škofja Loka - where it proved to be reliable and adaptable to local conditions. Results show that the GIS tool simplifies the work of spatial planners and supports sustainable urban development, as it facilitates monitoring urban growth and adjusting spatial policies based on precise building data. The development of such tools in Slovenia offers significant potential, as it enhances existing spatial data and allows for future improvements.